INNOVATIVE WAYS TO INCREASE THE COMPETITIVENESS OF THE TOURISM SECTOR IN THE COUNTRY - Abduazizov, Ilkhomjon Abduazizovich; Azimjonova, Fayyoza Farrukh qizi; Jurakulova, Shokhsanam Todjiddin qizi; Khudayberdiyeva , Sevinch Ibadullayevna (Educational Research in Universal Sciences, 2023)
This article analyzes the existing opportunities in the development of innovative technologies in the field of tourism. In particular, the level of use of Internet communication tools by potential consumers was studied, proposals were developed based on the results of research on the introduction of digital communications.